Acute acalculus cholecystitis and hepatitis caused by Brucella melitensis - Fawzia Eida AL-Otaibi (Journal of Infection in Developing Countries)
Acute cholecystitis is a very rare presentation of brucellosis. A case of acalculous cholecystitis caused by Brucella melitensis is reported with a review of previously reported cases.